2017
DOI: 10.1016/j.tiv.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of Caenorhabditis elegans (nematode) and Danio rerio embryo (zebrafish) as model systems to screen for developmental and reproductive toxicity of Piperazine compounds

Abstract: A B S T R A C TTo enable selection of novel chemicals for new processes, there is a recognized need for alternative toxicity screening assays to assess potential risks to man and the environment. For human health hazard assessment these screening assays need to be translational to humans, have high throughput capability, and from an animal welfare perspective be harmonized with the principles of the 3Rs (Reduction, Refinement, Replacement).In the area of toxicology a number of cell culture systems are availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In the present study, the reduction in the body area of the worms after exposure to piperazine designer drugs is an indicative of neurotoxicity. In a previous study, nematodes exposed to piperazine and piperazine analogs showed a slight delay in development, compared with untreated worms (Racz et al, ). The C. elegans body size is influenced by environmental conditions, and the nervous system plays a crucial role in the development of nematodes.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, the reduction in the body area of the worms after exposure to piperazine designer drugs is an indicative of neurotoxicity. In a previous study, nematodes exposed to piperazine and piperazine analogs showed a slight delay in development, compared with untreated worms (Racz et al, ). The C. elegans body size is influenced by environmental conditions, and the nervous system plays a crucial role in the development of nematodes.…”
Section: Discussionmentioning
confidence: 87%
“…There are other recent toxicity model developments that offer potential as alternatives. For example, the preliminary developmental and reproductive toxicity assay was developed (National Centre for the Replacement Refinement & Reduction of Animals in Research ) with 2 models based on nematodes and zebrafish as alternatives to mammals for product screening (Racz et al ). More recently, the zebrafish model was used to screen contaminated groundwater samples for reproductive toxicity based on phenotypic changes (developmental delays and malformations) during the first 96 h in the developing zebrafish larvae (G. Whale, personal communication).…”
Section: Moving Beyond Traditional Effluent Test Endpointsmentioning
confidence: 99%
“…There are other recent toxicity model developments that offer potential as alternatives. For example, the preliminary developmental and reproductive toxicity assay was developed (National Centre for the Replacement Refinement & Reduction of Animals in Research 2017) with 2 models based on nematodes and zebrafish as alternatives to mammals for product screening (Racz et al 2017). More recently, the zebrafish model was used to screen contaminated groundwater samples for reproductive toxicity based on phenotypic changes (developmental delays Detection/testing of estrogen-, androgen-, and thyroid-active chemicals in various systems (e.g., cell lines, primary cells, fish/frog embryos, yeast, and cell-free systems) Alternative assays that measure effects directly mediated by receptor binding or resulting from interference with hormone synthesis In vitro assays for testing acute toxicity Cytotoxicity tests with established fish cell lines Tests to explore toxicity pathways at the molecular and cellular levels PBTK models In vitro assays for testing genotoxicity Cellular/DNA damage exhibited as mutagenicity In vitro biomarker assays Cell lines (lower biological organizational level).…”
Section: Specific Considerations For the Application Of Various Methomentioning
confidence: 99%
“…For example, the potential of some of these test systems has recently been investigated as part of a National Centre for the Replacement, Refinement & Reduction of Animals in Research (NC3Rs; UK) challenge (National Centre for the Replacement, Refinement & Reduction of Animals in Research). Using research from this challenge from nematode ( Caenorhabditis elegans ) and zebrafish models have been shown to have potential to screen for mammalian relevant pre–development and reproductive toxicity phenotypic endpoints (Racz et al ). The pre–development and reproductive toxicity challenge omics results also indicated development and reproductive toxicity–specific responses on RNA and protein level and that 4‐RNAi in C. elegans indicated critical genes for toxicological response, although these results are yet to be published.…”
Section: Using Omics To Reduce Animal Use In Health and Environmentalmentioning
confidence: 99%